ASSESSMENT OF KNOWLEDGE, SELF-CARE PRACTICES AND FACTORS INFLUENCING POOR GLYCEMIC CONTROL AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS AT THU DUC GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to evaluate the level of disease knowledge and self-care practices, and to identify factors associated with poor glycemic control among patients with type 2 diabetes.Methods: A cross-sectional descriptive study was conducted on 357 outpatients with type 2 diabetes at Thu Duc General Hospital. Disease knowledge and self-care practices were assessed using the DKQ and the SDSCA measure, respectively.Results: A high prevalence of poor glycemic control (HbA1c ≥ 7%) was observed in 62.7% of participants. The mean DKQ score was 52.0 ± 10.8, and the median SDSCA score was notably low at 1.0 day/week. Multivariate logistic regression analysis identified insulin therapy (OR = 5.0), number of glucose-lowering medications (OR = 2.8), female sex (OR = 1.9), and poor medication adherence (OR = 1.8) as significant risk factors for failing to achieve glycemic targets. Conversely, self-management capacity demonstrated an independent protective effect: disease knowledge (OR = 0.95; p = 0.015) and self-care practices (OR = 0.72; p = 0.025).Conclusion: The majority of patients exhibited inadequate glycemic control, strongly associated with deficiencies in disease knowledge and self-care skills. Multivariate analysis confirmed that robust self-management capacity served as an independent protective factor. In contrast, female sex and a high treatment burden significantly increased the risk of therapeutic failure. These findings highlight the critical need to transition current outpatient management models from a strictly pharmacological focus to a comprehensive approach integrating patient health education.
Keywords: Type 2 diabetes, DKQ, disease knowledge, SDSCA, self-care.